1981
DOI: 10.1136/jcp.34.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Busulphan lung in childhood.

Abstract: A child receiving busulphan treatment for adult-type chronic myeloid leukaemia responded well for four years before the onset of complications leading to "busulphan lung'. Pulmonary function tests (PFT) were useful in monitoring the development of this condition and we recommended regular PFT for patient receiving busulphan treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Although not specifically evaluated, many of the patients in our study were treated with corticosteroids before death suggesting that the pulmonary toxicity was not reversible with corticosteroids. The 3.6% incidence of pulmonary mortality seen in our study is similar to that reported after standard doses of busulfan (10, 11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although not specifically evaluated, many of the patients in our study were treated with corticosteroids before death suggesting that the pulmonary toxicity was not reversible with corticosteroids. The 3.6% incidence of pulmonary mortality seen in our study is similar to that reported after standard doses of busulfan (10, 11).…”
Section: Discussionsupporting
confidence: 91%
“…Pulmonary toxic reactions after high‐dose BCNU are well described and amenable to treatment with corticosteroids (7, 8). Chronic administration of busulfan in standard doses is also known to cause pulmonary toxicity in approximately 4% of patients and manifests as delayed pulmonary fibrosis not amenable to treatment with corticosteroids (10, 11). Our study suggests that high‐dose busulfan may also be associated with pulmonary mortality after ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…The action of BU on cells is mainly limited to the bone marrow. However, other reported side effects of BU therapy are interstitial pulmonary fibrosis (busulphan lung), hyperpigmentation of the skin, ovarian suppression and amenorrhea, and cataract formation (Leake et al 1963;Burns et al 1970;Oakhill et al 1981;Reynolds 1993;Dollery 1999). BU is potentially teratogenic and carcinogenic (Feingold and Koss 1969;IARC 1987;Reynolds 1993;Dollery 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Regarding pulmonary lesions, it has been reported in humans that long-term and/or high-dose busulfan therapy brought about such pulmonary lesions as bronchopulmonary dysplasia and diffuse interstitial pulmonary fibrosis in adults 9 , 10 , 11 and children 1 , 2 . These lesions are known as “busulfan lungs.” In the lungs of fetal 6 and infant rats, only transient apoptotic changes were detected in alveolar and terminal bronchiolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In children, there are several reports of diverse effects of busulfan treatment such as pulmonary fibrosis and acute clinical neurotoxicity (spasm) 1 , 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%